The pelagic habitat analysis module for ecosystem‐based fisheries science and management. (23rd January 2017) - Harrison, Daniel P.; Hinton, Michael G.; Kohin, Suzanne; Armstrong, Edward M.; Snyder, Stephanie; O'Brien, Frank; Kiefer, Dale K.
Abstract: We have developed a set of tools that operate within an aquatic geographic information system to improve the accessibility, and usability of remote‐sensed satellite and computer‐modeled oceanographic data for marine science and ecosystem‐based management. The tools form the Pelagic Habitat Analysis Module (PHAM), which can be applied as a modeling platform, an investigative aid in scientific research, or utilized as a decision support system for marine ecological management. Applications include fisheries, marine biology, physical and biological oceanography, and marine spatial management. The GIS provides a home for diverse data types and automated tools for downloading remote sensed and global circulation model data. Within the GIS environment, PHAM provides a framework for seamless interactive four‐dimensional visualization, for matching between disparate data types, for flexible statistic or mechanistic model development, and for dynamic application of user developed models for habitat, density, and probability predictions. Here we describe PHAM in the context of ecosystem‐based fisheries management, and present results from case study projects which guided development. In the first, an analysis of the purse seine fishery for tropical tuna in the eastern Pacific Ocean revealed oceanographic drivers of the catch distribution and the influence of climate‐driven circulation patterns on the location of fishing grounds. To support management of the Common Thresher Shark ( Alopias vulpinus ) in the California Current Ecosystem, a simple empirical habitat utilization model was developed and used to dynamically predict the seasonal range expansion of common thresher shark based on oceanographic conditions.